Antireflux mucosectomy band in treatment of refractory gastroesophageal reflux disease: a pilot study for safety, feasibility and symptom control - Monino, Laurent; Gonzalez, Jean-Michel; Vitton, Véronique; Barthet, Marc (Endoscopy International Open, 2020)
Background and study aims Antireflux mucosectomy band ligation (ARM-b) is an endoscopic procedure that mimics a fundoplication for managing gastroesophoageal reflux disease (GERD). The aim of this study was to assess safety and feasibility of ARM-b.Patients and methods This was a single-center study on consecutive patients operated between June 2017 and January 2019 with refractory GERD, confirmed with pH-metry and without motility disorder at high-resolution manometry. A piecemeal mucosectomy of three quarters of circumference of esophagogastric junction was performed using a band ligation system and a hexagonal snare. The primary objective was to assess procedural safety and feasibility. The secondary objective was to document the clinical improvement at 3 and 6 months based on patient satisfaction, proton pump inhibitor (PPI) intake, symptoms, and quality of life scores.Results Twenty-onepatients (11 men) with mean age 56.9 ± 14.4 years were analyzed. The technical success rate was 100 % (mean duration 35 ± 11 min). Four patients (19 %) had mild adverse events: one delayed bleeding at Day 1 managed conservatively, and three dysphagia endoscopically managed. Mean follow-up was 10 ± 5 months. Decrease/discontinuation of PPI intake was 76 % at 3 months and 72 % at 6 months. Improvement in mean symptoms and quality of life scores (GERD-Q and GERD-HQL) were statistically significant. One patient required laparoscopic fundoplication after ARM-b failure without complication.Conclusion ARM-b is safe, feasible, and symptom-effective for treating refractory GERD, and it can be performed in the ambulatory setting. Further prospective studies are required to confirm these promising outcomes.